Communicating What We Know and What Isn't So: Science Communication in Psychology. (November 2021) - Lewis, Neil A.; Wai, Jonathan
The field of psychology has a long history of encouraging researchers to disseminate their findings to the broader public. This trend has continued in recent decades in part because of professional psychology organizations reissuing calls to "give psychology away." This recent wave of calls to give psychology away is different because it has been occurring alongside another movement in the field—the credibility revolution in which psychology has been reckoning with metascientific questions about what exactly psychologists know. This creates a dilemma for the modern psychologist: How is one to "give psychology away" if one is unsure about what is known or what one has to give? In the current article, we discuss strategies for navigating this tension by drawing on insights from the interdisciplinary fields of science communication and persuasion and social influence.